The Role of Medicinal Plants in Treating Intestinal Parasites: Peran Tanaman Obat dalam Pengobatan Parasit Usus - Amal Fadil Noori Radi; Ziyad Khalaf Hamdan; Noor Talal Ali (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Intestinal parasites remain a major global health concern, particularly in developing regions with poor sanitation and healthcare conditions. Specific Background: Conventional antiparasitic drugs are widely used but are associated with side effects and increasing drug resistance. Knowledge Gap: Limited integration of evidence regarding the mechanisms and therapeutic potential of medicinal plants as alternative treatments persists. Aims: This review examines the role of medicinal plants in combating intestinal parasites, focusing on their bioactive compounds and mechanisms of action. Results: Evidence from laboratory, animal, and limited clinical studies indicates that plants such as Zingiber officinale, Thymus vulgaris, Eucalyptus globulus, Aloe vera, Allium sativum, Artemisia herba-alba, and Nerium oleander exhibit inhibitory effects on parasite growth, reproduction, and survival, alongside immune modulation and anti-inflammatory activity. Novelty: The study synthesizes diverse findings on plant-derived compounds and highlights their multifunctional antiparasitic mechanisms. Implications: Medicinal plants represent promising complementary or alternative therapeutic options, though further clinical validation and standardization are required to ensure safety and efficacy. Keywords: Intestinal Parasites, Medicinal Plants, Antiparasitic Compounds, Bioactive Metabolites, Herbal Therapy Key Findings Highlights Multiple plant species demonstrate parasite growth suppression and immune modulation Bioactive compounds target parasite metabolism and cellular integrity Natural therapies show potential as complementary treatment strategies